2012
DOI: 10.1603/an12021
|View full text |Cite
|
Sign up to set email alerts
|

A New Species of Saphonecrus (Hymenoptera, Cynipoidea) Associated with Plant Galls on Castanopsis (Fagaceae) in China

Abstract: A new cynipid species, Saphonecrus hupingshanensis Liu, Yang, et Zhu, sp. nov. (Hymenoptera: Cynipidae: Synergini), is described from China. This is the first species of the inquilinous tribe Synergini ever known to have an association with chinquapins (Fagaceae: Castanopsis). The biology and implication to species diversity of Cynipidae in eastern and southeast Asia are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…All Synergus species have lateral pronotal carinae, except S. plagiotrochi, S. variabilis, S.flavipes, S. acsi, S. palmirae, and S. castaneus. The genus Saphonecrus includes 21 species (Wang et al 2010, Liu et al 2012, nine of which are found in the eastern Palaearctic region. Among these species, Saphonecrus diversus, Saphonecrus exdsus, Saphonecrus flavotibialis, Saphonecrus naiquanlini, and Saphonecrus yukawai have the female antenna with 11 fiagellomeres.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All Synergus species have lateral pronotal carinae, except S. plagiotrochi, S. variabilis, S.flavipes, S. acsi, S. palmirae, and S. castaneus. The genus Saphonecrus includes 21 species (Wang et al 2010, Liu et al 2012, nine of which are found in the eastern Palaearctic region. Among these species, Saphonecrus diversus, Saphonecrus exdsus, Saphonecrus flavotibialis, Saphonecrus naiquanlini, and Saphonecrus yukawai have the female antenna with 11 fiagellomeres.…”
Section: Discussionmentioning
confidence: 99%
“…castaneus is easily distinguishable from the seven species included in the genus Synophrus for the presence of lateral frontal carina (absent in Synophrus), the metasomal quadrangular shape (longer than head + mesosoma and longer than high in lateral view in Synophrus), and by the presence of sexual dichromatism (absent in Synophrus). Almost all species of Synergus and Saphonecrus are associated with Quercus galls caused by other cynipids, but Saphonecrus hupingshanensis (Liu et al 2012) emerged from galls on Castanopsis carlesii (Hemsl.) (Fagaceae) and Sa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Cyclobalanopsis has a widespread distribution in Asia, the gall-inducing cynipids have been restricted to Japan, Taiwan, and Vietnam (Ide et al , 2012(Ide et al , 2013Abe et al 2011;Tang et al 2011a,b;Melika et al 2013;Abe et al 2014). Despite increasingly intensive taxonomic studies being conducted on Mainland China over the past decade (Melika et al 2004;Wang et al 2010Wang et al , 2012Wang et al , 2013Liu et al 2012;Pujade-Villar and Wang 2012;Bernardo et al 2013), no cynipid wasps associated with Cyclobalanopsis have been reported in this region to date.…”
mentioning
confidence: 99%
“…The examination of the detailed description and illustrations of this species showed that it is not a Saphonecrus but a Synergus species: Synergus hupingshanensis (Liu, Yang & Zhu) which belongs to the group of Synergus species (Synergus castaneus, S. plagiotrochi and S. kawakamii) with partially open radial cell of the fore wing (Schwéger et al 2015a). This species is associated with galls developing on Castanopsis carlesii which from Liu et al (2012) never reared any gallwasp, thus they do not exclude the possibility that S. hupingshanensis might be a gall inducer . Such is the case with Synergus itoensis Abe, Ide & Wachi (Abe et al 2011).…”
Section: Synergus Hakonensismentioning
confidence: 98%